The application of (Y,Gd)BO3:Tb3+ and CaGa2S4:Mn2+ phosphors to remote white light-emitting diodes - Thuc Minh Bui; Nguyen Thi Phuong Loan; Phan Xuan Le; Nguyen Doan Quoc Anh; Anh Tuan Le; Le Van Tho (Universitas Ahmad Dahlan, 2020)
The remote phosphor structure is superior to the conformal phosphor and the in-cup phosphor in terms of lighting efficiency; however, managing the color quality of the remote phosphor structure has been a nuisance to the manufacturers. To address this problem, many researches were conducted and the results suggested that using dual-layer phosphor structure and triple-layer phosphor structure could improve the color quality in remote phosphor structures. The purpose of this article is to study which one between the two configurations mentioned above allows multi-chip white LEDs (WLEDs) to reach highest indexes in color rendering index (CRI), color quality scale (CQS), luminous flux (LF), and color uniformity. The color temperature of the WLEDs used for the experiments in this article is 8500 K. The result of this research shows that the triple-layer phosphor configuration has higher CRI, CQS, and LE and also able to reduce color deviation resulting in better color uniformity. This conclusion can be verified by analyzing the scattering features of the phosphor layers using the Mie-theory. Being verifiable increases the reliability of the research result and makes it a valuable reference for producing better quality WLEDs.